[RETRACTED] Conflict in Private Land: The Role of “Yellow Journalism” in the Turmoil of Batu Ceper, Tangerang 1934 - Muhamad Mulki Mulyadi Noor; Susanto Zuhdi (Indonesian Historical Studies, 2020)
RETRACTION NOTICE to the article entitled "Conflict in Private Land: The Role of “Yellow Journalism” in the Turmoil of Batu Ceper, Tangerang 1934" by M. Mulki Mulyadi Noor and Susanto Zuhdi which had been published at IHiS (Indonesian Historical Studies), Vol. 4 No. 2 (2020). This article has been retracted. Concern has been raised about the authorship dispute between the first author (corresponding author) and co-author, which is contrary to the journal policy according to COPE.As such this article represents a conflict of interest among the author. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.